2008
DOI: 10.1016/j.ydbio.2008.08.002
|View full text |Cite
|
Sign up to set email alerts
|

A transcriptional network coordinately determines transmitter and peptidergic fate in the dorsal spinal cord

Abstract: Dorsal horn neurons express many different neuropeptides that modulate sensory perception like the sensation of pain. Inhibitory neurons of the dorsal horn derive from postmitotic neurons that express Pax2, Lbx1 and Lhx1/5, and diversify during maturation. In particular, fractions of maturing inhibitory neurons express various neuropeptides. We demonstrate here that a coordinate molecular mechanism determines inhibitory and peptidergic fate in the developing dorsal horn. A bHLH factor complex that contains Ptf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
84
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 63 publications
3
84
0
1
Order By: Relevance
“…Another transcription factor Ptf1a acts to suppress Tlx3 expression and promote GABAergic differentiation (Glasgow et al, 2005;Mizuguchi et al, 2006;Hori et al, 2008). Three studies including ours have also shown that the transcription factors that determine the glutamatergic or GABAergic cell fate also control the expression of distinct sets of peptides in the dorsal horn selectively (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 53%
See 3 more Smart Citations
“…Another transcription factor Ptf1a acts to suppress Tlx3 expression and promote GABAergic differentiation (Glasgow et al, 2005;Mizuguchi et al, 2006;Hori et al, 2008). Three studies including ours have also shown that the transcription factors that determine the glutamatergic or GABAergic cell fate also control the expression of distinct sets of peptides in the dorsal horn selectively (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008).…”
Section: Introductionmentioning
confidence: 53%
“…Furthermore, whether other transmitter receptor genes in general are controlled by Tlx1/3 or Ptf1a is unknown. Previous studies have also characterized the transcriptional regulation of peptides in glutamatergic and GABAergic neurons (Bröhl et al, 2008;Huang et al, 2008;Xu et al, 2008). In this study, we have further shown that two genes encoding additional peptides, adenylate cyclase activating polypeptide 1 (PACAP/Adcyap1) and neurotensin (NT), are controlled by Tlx1/3.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Néanmoins, plusieurs populations ont pu être identifiées chez l'adulte sur la base de l'expression de neuropeptides et de diverses protéines. Ainsi certains neuropeptides (comme la somatostatine, la substance P ou la neurotensine) ou des protéines fixant le calcium (la calbindine et la calrétinine) ont été identifiés dans des sous-types d'interneurones excitateurs alors que d'autres (le neuropeptide Y [NPY], la galanine, la parvalbumine) sont majoritairement exprimés dans des sous-types de neurones inhibiteurs [3,4] (Figure 1B Figure 1C) qui permet de manipuler génétique-ment la plupart de ces interneurones. Il est en effet maintenant possible 3 L'intersection de l'expression de différents gènes dans une même population cellulaire permet, grâce à l'utilisation de souris géné-tiquement modifiées exprimant différentes recombinases sous le contrôle de ces gènes, de les cibler spécifiquement.…”
unclassified